2020
DOI: 10.1016/j.jpainsymman.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aliviado Dementia Care—Hospice Edition Training Program on Hospice Staff's Dementia Symptom Knowledge

Abstract: Context. As the aging population grows, the incidence of dementia continues to increase substantially. However, the lack of a significant geriatric health care workforce as well as little dementia training among generalist health care workers leads to suboptimal care for persons living with dementia (PLWD). In particular, few evidence-based interventions exist to improve the quality of dementia care among hospice interdisciplinary teams caring for PLWD. Aliviado Dementia CaredHospice Edition is a quality assur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…While this is the first program specifically designed to educate home health professionals on PD/PRD-specific needs, similar interventions have been successful in other geriatric populations [ 36 , 37 ]. Fukui and colleagues conducted a cluster randomized trial of an educational booklet and workshop on end-of-life issues for home care nurses, care managers, and care workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this is the first program specifically designed to educate home health professionals on PD/PRD-specific needs, similar interventions have been successful in other geriatric populations [ 36 , 37 ]. Fukui and colleagues conducted a cluster randomized trial of an educational booklet and workshop on end-of-life issues for home care nurses, care managers, and care workers.…”
Section: Discussionmentioning
confidence: 99%
“…Greater recognition and empathy for neuropsychiatric symptoms "Being more sensitive to what goes on inside the thought processes of someone experiencing Lewy body hallucinations" "Always putting myself in someone's position before making a decision and being patient because it is not who they are, but it is because of the disease they behave that way" Pharmacologic management and medication reconciliation "Having better knowledge of the function of levodopa… blood pressure and home care role" "Implementing more awareness on orthostatic hypotension with these patients as well as the importance of medication reconciliation" Non-pharmacologic symptom management "Trying tape for doorways and teaching BIG exercises" "Adding the sip-a-mug" students found that while neuroanatomy overall was ranked the most difficult anatomic system to learn, the motor pathways and basal nuclei-the structures most involved in PD/PRD-were ranked second and fifth most difficult, respectively, out of 21 topics in the neuroanatomy curriculum [22]. While this is the first program specifically designed to educate home health professionals on PD/PRD-specific needs, similar interventions have been successful in other geriatric populations [36,37]. Fukui and colleagues conducted a cluster randomized trial of an educational booklet and workshop on end-of-life issues for home care nurses, care managers, and care workers.…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of innovations aiming to improve end‐of‐life care for PWD. Programs like Aliviado Health aim to improve dementia expertise of clinicians within hospice, home health, and long‐term care models 34–36 . The UCLA Alzheimer's & Dementia Care co‐management program shows positive end‐of‐life outcomes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies assessed the effects of the interventions on participants' attitudes or stigma pertaining to ADRDs. Three studies used self-developed questionnaires to measure ADRD attitudes, three studies used the Dementia Attitudes Scale, 16,40,43 one study used the Attitudes of People from Ethnic Minorities to Help-Seeking for Dementia questionnaire, 26 one study used the DSKA, 44 and another study used the KAD. 28 Among the nine studies, three reported statistically significant improvement in attitudes using the Dementia Attitudes Scale.…”
Section: Attitudes Towards Dementiamentioning
confidence: 99%
“…Five studies did not report statistically significant changes in attitudes towards dementia. 10,26,36,41,44 Intervention satisfaction Intervention satisfaction was assessed in nine studies. 14,26,28,31,32,36,38,39,41 Intervention satisfaction was measured based on Likert-type scales (n = 2), interviews or focus groups (n = 6), and a single yes/no question.…”
Section: Attitudes Towards Dementiamentioning
confidence: 99%